Peningkatan Kesadaran Tentang Kenakalan Remaja: Seminar Kkn Di Mts Nurul Huda Desa Cikole - Al Ansori, Farid Munawar; Zakiyah, Hansa Mutia; Maharani, Silva Elvira; Syarawi, Siti Huda (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Education and the school environment are very important places for the development of children and adolescents. However, in addition to positive challenges, the school environment also faces serious problems such as drugs, sexual harassment and bullying. In the Real Work Lecture (KKN) work program by the 325 UIN Bandung group, providing outreach to the younger generation regarding the importance of increasing awareness and knowledge about "Prevention of Drugs, Sexual Harassment and Bullying in the School Environment" as well as developing effective strategies to prevent and overcome they. This socialization activity was carried out at Nurul Huda Middle School, RW 08, Cikole Village, Lembang District, West Bandung Regency. The method for implementing this socialization uses a method which places more emphasis on aspects of in-depth understanding of a problem rather than looking at the problem for generalization research. This program was carried out by KKN 325 Cikole students in 3 classes, from grades VII-IX students and also teachers who took part in the seminar. Participants were attended by all classes to include involvement in education and support for teenagers, as well as interest in the problem of teenage acquaintances.